General Anesthesia pada Tindakan Sirkumsisi Pasien Phimosis dengan Sindrom Nefrotik - Ayundira Nur Usradti (CV. ITTC INDONESIA, 2026)
Pathological phimosis is one of the primary indications for circumcision in children. Anesthetic management in pediatric patients with nephrotic syndrome requires special consideration due to altered drug pharmacokinetics, fluid balance disturbances, and an increased risk of infection associated with long-term corticosteroid therapy. Case Report: We report the case of a 12-year-old boy diagnosed with pathological phimosis and nephrotic syndrome in remission who underwent elective circumcision under general anesthesia. The patient presented with an inability to retract the foreskin accompanied by painful urination for four months. Laboratory findings revealed leukocytosis, 2+ proteinuria, and a serum albumin level of 2.8 g/dL. The patient was classified as American Society of Anesthesiologists (ASA) Physical Status II. General anesthesia was induced with fentanyl and propofol and maintained with sevoflurane, while intraoperative fluid therapy was administered using Ringer's lactate according to calculated requirements. Hemodynamic parameters remained stable throughout the procedure without anesthetic or surgical complications. The patient recovered uneventfully with an Aldrete Score of 11 and was discharged on the third postoperative day after satisfactory clinical improvement. Conclusion: Successful anesthetic management of pediatric patients with pathological phimosis and nephrotic syndrome depends on comprehensive preoperative assessment, appropriate anesthetic agent selection, careful intraoperative fluid management, and meticulous perioperative monitoring. A multidisciplinary approach contributes to favorable clinical outcomes while minimizing perioperative complications.